Analysis Of The Influence Of Social Demographics, Financial Knowledge, And Financial Attitude On Investment Decisions (Case Study On Employees Of The Republic Of Indonesia Financial Audit Agency) - Susi Megawati; Eko Sembodo; Wardojo (LPPM Universitas Respati Indonesia, 2024)
Behavioral finance is a science that studies how humans respond and react to existing information which is then used to make investment decisions by paying attention to the risks inherent therein. The aim of this research is to find out how socio-demographic factors, financial literacy and financial attitude influence investment decisions among employees of the Supreme Audit Agency. The research method uses a quantitative approach with a questionnaire instrument, purposive sampling data collection techniques with 100 respondents, and Structural Equation Modeling (SEM) analysis methods. Based on the results of this research, it confirms: First, Social Demographic factors have a positive influence on investment decisions. Statistical test results show that 78% of investment decisions are influenced by socio-demographic factors. From several indicator variables studied, it shows that the income factor is an important factor in the socio-demographic variables, then the age maturity and education factors. Second, financial knowledge (financial literacy) has a positive and significant influence on investment decisions. Statistical test results show that 85% of investment decisions are influenced by financial knowledge. In this case, the investment knowledge factor is the strongest factor of financial knowledge for investment decision purposes. It is clear that financial attitude has a positive effect on investment decisions. Statistical test results show that 63% of investment decisions are influenced by the respondent's financial attitude. In this case, the cognitive aspect makes an important contribution to financial attitudes. This means that the individual's beliefs or attitudes towards finances are quite good. Then the behavioral aspect in applying finance and finally the affective aspect or the individual's emotional attitude towards finance. Keywords: Social Demographics, Financial Knowledge, Financial Attitudes, Investment Decisions.